Implementasi Pembelajaran Active Learning Pada Mata Pelajaran Aqidah Akhlak - Huda, Aksin Nurul; Ma`arif, Muhammad Anas (Edukasi: Journal of Educational Research, 2021)
The purpose of this article is to analyze and discuss the implementation of Active Learning in learning Akidah Akhlak class XI at Madrasah Aliyah (MA) Darul Ulum Baureno Bojonegoro. This article uses qualitative research with a case study approach. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and verification/drawing conclusions. While the validity of the data using the triangulation technique. The results of this study are as follows: The implementation of Active learning in Aqidah Akhlaq learning in class XI at MA Darul Ulum Pasinan Baureno Bojonegoro has been carried out in three stages, namely planning, implementation and evaluation. Factors that hinder the implementation of active learning in Aqidah Akhlaq class XI learning at MA Darul Ulum Baureno Bojonegoro are the lack of student response to learning, differences in student backgrounds, and characteristics, learning time at the end of learning which makes students lack focus and concentration during activities ongoing.